Seton drainage combined with anti-TNF therapy for perianal fistulizing Crohn's disease, single center experience - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Objective: The aim of this study was to evaluate the efficacy of combined treatment with anti-tumor necrosis factor (TNF) agents, and setons for perianal fistulas in Crohn's disease. Patients and Methods: Study included 27 consecutive patients with perianal fistulizing Crohn's disease, requiring seton drainage and anti-TNF therapy in our center from January 2013 to November 2014. All patients underwent a standardized pelvic magnetic resonance imaging (MRI) examination. Patient characteristics, follow up time, findings of pelvic MRI, colonoscopy and examination under anesthesia findings were recorded. Response to treatment was evaluated at the end of the follow up. Results: The median follow-up after treatment was 17 months (6-32). The fistula was complex in 24 (89%) of the 27 patients. Colonoscopy revealed ileitis in 16 (59.3%) patients and active proctitis in 9 (33.3%) patients. Perianal abscess was observed in 12 (44.4%) patients. Complete response was obtained in 17 (63%) patients. Only 3 (11.1%) patients experienced recurrence abscess during the study period. We could not find any factor, which were associated with complete response. Conclusion: Complete response was achieved in 63% of the patients, with perianal fistula formation associated with Crohn's disease, with combined seton drainage and anti-TNF therapy.
Keywords: Crohn's disease; Perianal fistula; Setons; Infliximab